Cost-effectiveness of high-dose vitamin D supplementation to reduce the occurrence of repeat episodes of pneumonia in children - Jefferson Antonio Buendía; Diana Guerrero Patiño (Cost Effectiveness and Resource Allocation, 2024)
Abstract Introduction Despite the growing evidence on efficacy, little is known regarding the efficiency of Vitamin D supplementation (VDS) to reduce the incidence of repeat episodes of pneumonia in children. This study aimed to determine the cost-utility of VDS to reduce the incidence rate of repeat episodes of pneumonia in children. Methods A decision tree model was used to estimate the cost and quality-adjusted life-years (QALYs) of VDS in a patient aged 2 to 60 months with a clinical diagnosis of community-acquired pneumonia requiring in-hospital management. Multiple sensitivity analyses were conducted to evaluate the robustness of the model. Cost-effectiveness was evaluated at a willingness-to-pay (WTP) value of US$5180. Results The QALYs per person were 0,93 with VDS and 0,92 without VDS. The total costs per person were US$ 1148 for VDS and US$ 1284 without VDS. This position of absolute dominance of VDS makes it unnecessary to estimate the incremental cost-effectiveness ratio. The ICER was sensitive to changes in the relative risk of Vitamin D supplementation. Conclusion In conclusion, our study shows that VDS is a cost-effective to reduce the incidence rate of repeat episodes of pneumonia in children, from a societal perspective. However, the sensitivity of ICER to relative risk makes it necessary to take the results of this economic evaluation with caution.